PEMBERDAYAAN KELOMPOK PENDUKUNG AIR SUSU IBU (KP-ASI) SEBAGAI UPAYA PENCEGAHAN STUNTING DI WILAYAH KERJA PUSKESMAS NGAMPEL KABUPATEN KENDAL - Surani, Endang; Rosyidah, Hanifatur (P3M Universitas Aisyiyah Surakarta, 2025)
Low coverage of exclusive breastfeeding can cause a high incidence of stunting. This is influenced by the mother's education, family income, mother's knowledge about nutrition, exclusive breastfeeding, age at which MPASI is given, adequate levels of zinc and iron, history of infectious diseases and genetic factors. Education about exclusive breastfeeding is still limited to posyandu and there is not much use of independent community forums such as breastfeeding support groups (KP ASI). Therefore, it is necessary to empower breastfeeding support groups in the working area of the Ngampel Community Health Center, Kendal Regency through providing education regarding breast milk. The solution planned through community service is increasing breastfeeding mothers' knowledge about the importance of exclusive breastfeeding, how to express breast milk, how to store expressed breast milk, and relaxation. The results of the implementation of the activity showed an increase in knowledge of breastfeeding mothers regarding 4 materials related to exclusive breastfeeding for KPASI members with an average score of 50.28 increasing to 64.14 after providing education. Keywords: Education; exclusive breastfeeding;KP-ASI